2000
DOI: 10.1002/(sici)1097-0320(20000215)42:1<11::aid-cyto3>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte subsets and specific T-cell immune response in thalassemia

Abstract: Infection is very common in thalassemia and is one of the major causes of death. To date, it is not quite clear why these patients are susceptible to infection. In this study, lymphocyte immunophenotyping for CD3+ (T‐cells), CD3+CD4+ (T‐helper/inducer cells), CD3+CD8+ (T‐suppressor/cytotoxic cells), CD3−CD19+ (B‐cells), and CD3−CD16/56+ (natural killer cells) subsets and expression of the activation antigen CD69 on CD3+CD4+ and CD3+CD8+ T‐cells were determined in the whole blood of thalassemia patients, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 21 publications
1
9
1
Order By: Relevance
“…Although some investigators have not found differences in the activation status of peripheral blood lymphocytes [3,4,5,6,7], our results clearly show that our patients, with transfusion-dependent thalassemia, have increased numbers of activated peripheral blood cells. The majority of our patients have received more than 50 blood units throughout their life, and no correlation was found between the activation status and the number of transfusions.…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations
“…Although some investigators have not found differences in the activation status of peripheral blood lymphocytes [3,4,5,6,7], our results clearly show that our patients, with transfusion-dependent thalassemia, have increased numbers of activated peripheral blood cells. The majority of our patients have received more than 50 blood units throughout their life, and no correlation was found between the activation status and the number of transfusions.…”
Section: Discussioncontrasting
confidence: 48%
“…In another report, the levels of sICAM predicted graft rejection in transplanted thalassemics [14]. The reason(s) for this phenomenon is not well investigated, but iron overload, transfusions, infectious agents, red blood cell (RBC) rheological properties, and factors derived from increased RBC destruction may play a significant role [1,4,7,8,9,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides predisposing to infections by encapsulated bacteria, splenectomy has also been correlated with immune system modifications, including quantitative lymphocyte changes without any functional impairment, as well as aggravation of the immunological effects of multiple transfusions, due to the reduced immune clearance (Pattanapanyasat et al, 2000).…”
Section: Discussionmentioning
confidence: 99%